The moderating effect of marital conflict on the relationship between social avoidance and socio-emotional functioning among young children in suburban China - Zhu, Jingjing; Liu, Mowei; Shu, Xin; Xiang, Shuhui; Jiang, Yaoqin; Li, Yan (Frontiers in Psychology, 2022)
The goal of the present study was to examine the moderating effect of marital conflict in the link between social avoidance and indices of socio-emotional functioning among young children in mainland China. Participants were N = 256 children aged from 49-72 months (125 boys, 131 girls, Mage = 59.06 months, SD = 6.58) attending preschool/kindergartens from suburban areas in Shanghai, People’s Republic of China. Multi-source assessments were employed, with mothers reporting marital conflict as well as rating their children’s social withdrawal (i.e., social avoidance, shyness, unsociability), and teachers assessing indices of children’s socio-emotional functioning at school (i.e., anxious-fearful behavior, peer exclusion, and loneliness). Children were interviewed about their loneliness. Among the results, social avoidance was positively associated with anxious-fearful behavior, peer exclusion, and loneliness (marginal significance). Moreover, as hypothesized, marital conflict was found to exacerbate the relations between social avoidance and peer exclusion, and loneliness. Results are discussed in terms of the etiology and implications of social avoidance among young children in mainland China.